Respiratory Carcinogenesis - Pokorski, Mieczyslaw.; Pokorski, Mieczyslaw. (Neuroscience and Respiration ;, 2015)
The book blends basic and clinical research on respiratory carcinogensis. The contributions tackle a variety of respiratory-related cancers, notably non-small cell lung carcinoma, pleural mesothelioma, mediastinal tumors, or larynx cancer. The focus is on the search for novel molecular markers, derived from easily accessible tissues in clinical settings, such as the serum or bronchoalveolar lavage fluid, which could help diagnose cancer at an early stage and have a prognostic therapeutic value. The transcriptional mechanisms which endow cells with the capacity for unlimited proliferation are considered, with silencing of tumor suppressor genes is the exemplar. Chapters provide insight into a variety of cancer-related disorders of the respiratory tract, novel ways of differential diagnosis and treatment. The aim is to bring the current clinical procedures into alignment with the latest basic research findings. The book is a text for respiratory researchers, clinicians, and pathologists.